(3GdeQGLYI GdNGQLjI (B:s (3ehVhYGJ eJNUUI (B/s - (3GdUMf, YHO GdaJGM eMeOs; (3cGed, SejQs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2000)
(3Yde GdeQGLYI(B- (3CSGdjH GdeYGjfI GdEMUGFjI aj GdeQGLYI(B- (3GdELQGAGJ GdJMdjdjI aj GdeQGLYI GdaMU GdNGU(B- (3GdeQGLYI GdEOGQjI(B- (3eQGLYI GdHfhc GdJLGQjI(B- (3GdLgGR GdeQcRj ddeMGSHGJ(B- (3GdeQGLYI aj Xd CfXeI GdJTZjd GdEdcJQhfj ddHjGfGJ(B- (3GdeQGLYI GdHjFjI(B.s
Keywords: (3GdEOGQIs; (3GdeMGSHIs; (3GdeQGLYIs